Rancang Bangun Sistem Informasi Perpustakaan Digital Berbasis Web Pada SDN Paku Jaya 2 - Ade Priadi; Muhammad Feizal (CV. Multi Kreasi Media, 2022)
Public Elementary School Paku Jaya 2 is an educational facility that facilitates the library. Located in Jl.Patal III Kp. Pondok serut No. 6 RT.09/RW.03, Paku Jaya Kec. Serpong Utara. Public Elementary School Paku Jaya 2 still using the conventional way of operation, starting from recording borrowing books to recapitulation of monthly reports. This sometimes leads to inaccuracies and ineffectiveness in recording. Public Elementary School Paku Jaya 2 this has the potential to be able to continue to develop its library. For this reason, this research aims to build a web-based digital library information system on to Public Elementary School Paku Jaya 2 in order to help students and teachers in finding information. In addition, the use of this digital library system is expected to increase the interest in reading and insight of students Public Elementary School Paku Jaya 2 to be good. The research method used is the method of data collection, Observations and interviews. System development methods used are prototype and UML (Unified Modeling Language). Tools Analysis and database design using Entity Relationship Diagram (ERD) and transformed to Logical Record Structure (LRS), Programming languages using PHP as well as databases using MYSQL. Testing methods using Blackbox testing. The result of this study was to produce a web-based digital library information system in order to help students and teachers in finding information. Like textbooks, folk tales and fairy tales.